Retraction: 'Effect of blonanserin on cognitive function in antipsychotic‐naïve first‐episode schizophrenia'. (1st June 2017) - Tenjin, Tomomi; Miyamoto, Seiya; Miyake, Nobumi; Ogino, Shin; Kitajima, Rei; Ojima, Kazuaki; Arai, Jun; Teramoto, Haruki; Tsukahara, Sachiko; Ito, Yukie; Tadokoro, Masanori; Anai, Kiriko; et al.
Abstract : The above article from Human Psychopharmacology, first published on 25 January 2012 in Wiley OnlineLibrary (onlinelibrary.wiley.com ), and in Volume 90, pp. 90‐100, has been retracted by agreement between the authors, the journal Editor in Chief, David Baldwin, and John Wiley & Sons Ltd. The retraction has been agreed following an investigation by the St Marianna University Ethics Committee which determined that the paper was not as originally designed and approved. REFERENCES: Tenjin, T., Miyamoto, S., Miyake, N., Ogino, S., Kitajima, R., Ojima, K., … Yamaguchi, N. (2012). Effect of blonanserin on cognitive function in antipsychotic‐naïve first‐episode schizophrenia. Hum. Psychopharmacol Clin Exp, 27, 90–100.https://doi.org/10.1002/hup.1276 .